Development and validation of an ultra-sensitive method for the measurement of plasma renin activity in human plasma via LC–MS/MS. (December 2012) - Chappell, Derek L; McAvoy, Thomas; Weiss, Barbra; Weiner, Russell; Laterza, Omar F
Background: Renin catalyzes the conversion of angiotensinogen to angiotensin I (Ang I), the first and rate-limiting step in the renin–angiotensin–aldosterone system. Plasma renin activity (PRA) is an important target engagement biomarker in the clinical development of renin inhibitors. We have developed and validated an improved PRA assay that incorporates an Ang I trapping antibody followed by extraction and quantification of Ang I using a highly sensitive and specific LC–MS/MS method.Results: The following assay performance characteristics were assessed as part of analytical validation: precision, LOQ, spike recovery, dilution linearity, stability, absolute recovery and biological variability. The assay demonstrated excellent performance characteristics. Notably, the sensitivity of the assay was increased 140-fold when compared with a previous enzyme immunoassay-based assay.Conclusion: The improved sensitivity allowed the measurement of >95% PRA inhibition from baseline levels. In addition, we compared the LC–MS/MS-based assay to an enzyme immunoassay-based assay.